Comparison of Ediacaran platform and slope δ238U records in South China: Implications for global-ocean oxygenation and the origin of the Shuram Excursion. (15th October 2020) - Cao, Mengchun; Daines, Stuart J.; Lenton, Timothy M.; Cui, Huan; Algeo, Thomas J.; Dahl, Tais W.; Shi, Wei; Chen, Zhong-Qiang; Anbar, Ariel; Zhou, Yao-Qi
Abstract: The Ediacaran Shuram negative carbon isotope excursion (SE) records major paleoceanographic changes during the late Neoproterozoic, possibly linked to a global oceanic oxygenation event, yet its cause(s) remain uncertain. Earlier studies of the upper Ediacaran Doushantuo Formation in South China based on local redox proxies have documented strong spatial redox heterogeneity along shelf-to-basin transects, but variations of δ 238 U (a global redox proxy) have not yet been examined in deep-water SE carbonates. In this study, we examined δ 238 U variations through the SE in the upper slope Siduping section. Similar to platform SE sections, Siduping exhibits a shift toward higher δ 238 U values correlative with the peak of the SE (i.e., maximum negative δ 13 Ccarb ), confirming inferences of global ocean oxygenation during the SE. This raises an apparent paradox, because a global negative carbon isotope excursion implies net oxidant consumption, requiring an ocean-based oxygenation mechanism. We hypothesize that an increase in the efficiency of phosphorus burial due to a plankton-driven shift from dominantly dissolved organic matter (DOM) cycling to greater particulate organic matter (POM) export depleted the ocean of nutrient phosphorus. By producing a steep redox gradient close to the sediment-water interface, we suggest that ocean oxygenation also triggered a globally simultaneous diagenetic event in which isotopically light δ 13 Ccarb was precipitated in authigenic carbonate minerals. This scenario can account for δ 238 U differences between shallow-water and deep-water carbonates, which reflect precipitation of relatively larger amounts of authigenic carbonate minerals in shallow-water settings, generating both a larger negative δ 13 Ccarb shift and a larger early diagenetic δ 238 U offset.